A general concept of fire hybrid modelling in compartments - Gałaj, Jerzy (Journal of Civil Engineering and Management, 2009)
A general concept of a hybrid modelling of fire dynamics in the compartments is presented. The hybrid fire model combines the advantages of both zone and field models. The assumptions applying to physical model of fire and its mathematical description are given. Some problems related to application and development as well as verification and validation of the model are discussed. Santrauka Aprašyta gaisro hibridinio modeliavimo bendroji koncepcija. Gaisro hibridinis modelis susieja zonų ir laukų modelių privalumus. Pateiktos fizikiniame modelyje naudojamos prielaidos, aprašyta matematinė modelio dalis. Aptarti kai kurie taikymo ir tobulinimo, kaip ir rezultatų patikrinimo ir patvirtinimo, ypatumai. Reikšminiai žodžiai: gaisro modeliavimas, kompiuterinė simuliacija, laukų gaisro modelis, hibridinis gaisro modelis, degimas.